Cluster of pregnancy‐associated melanoma: A case report and brief update. Issue 9 (18th June 2020) - Van Rooij, Nicholas; Adams, Agnieszka; De'Ambrosis, Brian; Nathan, Vaishnavi; Hayward, Nicholas; Whiteman, David
Abstract: Melanoma incidence is increasing globally with Australia having the highest incidence in the world. Pregnancy‐associated melanoma is recognized in the published work; however, significant knowledge deficiencies exist. We present the case of a 34‐year‐old woman with dysplastic nevus syndrome who over a 15‐year period developed a total of nine melanomas, with eight clustered around an 18‐month peri‐ to post‐partum period. The first eight lesions were in situ with the ninth lesion invasive. No metastatic disease was observed over the 18‐year follow‐up period. This case identifies the potential sensitivity of a subset of melanomas to pregnancy‐related factors, with particular relevance to the development of lesions in the post‐partum period. We suggest that patients with a history of any documented melanoma risk factors, particularly dysplastic nevus syndrome, require close monitoring especially during pregnancy and early post‐partum.